Potential significance of changes in serum levels of IL-17, TNF-α and DKK-1 in the progression of the rheumatoid arthritis - Qunxia Wang; Yanzhao Liu; Jiazhen Wu; Simei Chen; Tingting Hu; Yuhan Liu; Xu Li; Xiaohang Li; Yang Wu; Jianlin Yu; Tingting Zeng; Yi Luo; et al. (Autoimmunity, 2023)
AbstractTo detect the value of serum interleukin-17 (IL-17), tumour necrosis factor-α (TNF-α), and Dickkopf-1 (DKK-1) in rheumatoid arthritis (RA) at different disease stages. 141 RA patients were randomly obtained and diagnosed in a large tertiary first-class hospital in Jiangxi Province from November 2021 to January 2022. RA was divided into 38 low activity and remission phase (low remission patients), 72 moderate activity patients, 41 high activity patients, according to the disease activity score 28 (DAS28) of RA and 70 healthy controls. IL-17 and TNF-α in serum detected by flow cytometry; DKK-1by ELISA; rheumatoid factor (RF) and C-reactive protein (CRP) by rate scattering turbidimetry; erythrocyte sedimentation rate (ESR) by Widmanstat method; anti-cyclic citrullinated polypeptide antibody (Anti-CCP) by chemiluminescence. The changes among the groups were statistically analysed and evaluated their diagnostic value. ①Anti-CCP, CRP, and ESR levels in the moderate-to-high activity group were higher than controls, while IL-17, TNF-α, and DKK-1levels higher than low remission group, moderate activity group and controls (p < 0.05). ②IL-17, TNF-α and DKK-1 were positively correlated with RA disease activity, with the correlations of IL-17, TNF-α and DKK-1 all over 0.5 (p < 0.05). ③The ROC curve showed that among all indices the AUC of DKK-1 was the largest, 0. 922, and has the highest sensitivity and negative predictive value for RA, 0.965 and 0.953, respectively. The specificity and positive predictive value of TNF-α is highest, 0.918 and 0.921, respectively, combined them had the highest predictive value in moderate-to-high activity RA, with AUC of 0.968, and had the highest sensitivity of 0.965. The IL-17, TNF-α and DKK-1 levels were elevated in RA and positively correlated with disease activity, involved in the Wnt signalling pathway of inflammatory and joint destructive effects, combining them to monitor the RA disease process and biologically treat the cytokines in the pathogenesis of RA were valuable.